Proportion trends, cancer stage, and survival of patients with cancer diagnosed through emergency and nonemergency departments: a nationwide cohort study - Lin, Ying-Chao; Kuo, Wei-Yin; Kung, Pei-Tseng; Tsai, Wen-Chen (Frontiers in Oncology, 2024)
Introduction To reduce mortality, the Taiwan government has vigorously promoted free cancer screening and preventive health screening services. Cancers are usually advanced by the time they are discovered in the emergency department. Through this study, we aimed to understand the characteristics of cancer patients diagnosed through the emergency department and thus identify high-risk populations by comparing cancer staging and survival rates in patients diagnosed in the emergency department and those diagnosed in the non-emergency department. Methods The retrospective study enrolled a total of 389,043 patients over the age of 20 who were newly diagnosed with one of the five major cancers (including lung cancer, colorectal cancer, breast cancer, prostate cancer, and oral cancer) between 2008 and 2017 and analyzed their diagnostic pathway, cancer stage at diagnosis, and survival time. Results Of the study participants, 59,423 patients (about 15.3%) were diagnosed with cancer through the emergency department. We found that a sizable proportion of older people and patients with low education and low incomes were diagnosed through emergency department visits, and those with a health condition comorbidity severity of 3 had the highest proportion diagnosed by the emergency department, advanced stages at diagnosis, and risk of death. These can be classified as high-risk groups. In addition, 76.4% of patients diagnosed in the emergency department had advanced cancer, and the risk of death was 1.46 times higher than that of patients diagnosed in the non-emergency department. Although cancer screening is available, it does not reduce the proportion of patients with advanced cancer who are diagnosed through or at the time of diagnosis in the emergency department. Conclusions The present study found that the government’s cancer screening did not affect the proportion or number of cancers diagnosed through emergency department visits. Therefore, the government should focus on more cancer screening, health education in high-risk groups, and strengthening the link between emergency and oncology departments to reduce the risk of death for patients diagnosed through emergency department visits.